Water Use, Efficiency, and Stomatal Sensitivity in Eastern Cottonwood and Hybrid Poplar Varietals on Contrasting Sites in the Southeastern United States - Renninger, Heidi J.; Stewart, Leah F.; Rousseau, Randall J. (Frontiers in Forests and Global Change, 2021)
The southeastern United States (US) has widescale potential to achieve high productivity from elite eastern cottonwood and hybrid poplar varietals to produce renewable bioenergy and bioproducts. In order to determine how environmental drivers impact water use and growth so that individuals can maintain growth during drought periods, varietals that use water efficiently and/or tolerate water stress conditions are needed to make planting recommendations across a variety of sites. Additionally, inoculation with nitrogen-fixing endophytic bacteria may improve water stress tolerance. The goals of this research were 1) to determine water use strategies using measurements of diurnal sapflow and differences in leaf retention for three eastern cottonwood (Populus deltoides, ST66, S7C8, 110412) and three hybrid poplar (two P. deltoides × P. maximowiczii; 6329 and 8019, and one P. trichocarpa × P. deltoides, 5077) varietals on contrasting field sites, 2) determine the physiological impact of endophyte inoculation, and 3) determine which physiological parameters were most highly correlated with aboveground biomass. We found that whole-tree water use efficiency (WUE) was similar across varietals at 5.2 g biomass per kg water used and that water use scaled with tree size. We found that water use strategies in terms of scaled stomatal sensitivity to vapor pressure deficit converged across varietals under stressful soil water conditions at both sites, but that varietals 8019 and 110412 tended to exhibit the highest plasticity in stomatal sensitivity exhibiting the largest range in scaled stomatal sensitivity under different soil moisture conditions. Endophyte inoculation increased growth and stomatal sensitivity at the nitrogen-limited site. Leaf area, whole-tree WUE, and plasticity in stomatal sensitivity were correlated with aboveground biomass production across sites and varietals. Overall, these data can be used to model hydrologic impacts of large-scale Populus biofuel production as well as recommend varietals with efficient water use and stomatal sensitivity under a range of soil and atmospheric moisture stress factors.